Street skating : grinds and grabs - Savage, Jeff (Mankato, Minnesota : Capstone Press, 2005)
Describes street skating, a sport in which skateboarders do tricks on street courses and public parks and sidewalks.
Includes bibliographical references and index.
Keywords: Skateboarding -- Juvenile literature